Multi-Temporal UAV Photogrammetry and DEM Differencing for Landslide Deformation Monitoring in a Mining Area, Inner Mongolia - Hu, Jiayi; Cao, Chen (Journal of Progress in Civil Engineering, 2025)
This study investigates slope deformation in Baiyinhu No. 2 open-pit mine (Inner Mongolia Plateau) using multi-temporal UAV photogrammetric surveys conducted in June and September 2024. High-resolution full-frame imagery (GSD 6.3 cm) and precise POS data (GNSS/IMU, horizontal ±3 cm, vertical ±5 cm) were processed in Pix4D Mapper to generate orthoimages and DEMs. Model re-projection error ( 0.1 px), point cloud density (512 pts/m²), and GCP-based RMSE (horizontal 0.091 m, vertical 0.080 m) demonstrate robust geometric accuracy. DEM differencing revealed localized subsidence up to 0.9 m at the midsection and toe of the landslide. Additional analysis of four deformation bodies (April–September 2023) showed vertical displacements of 0.2–0.6 m. The observed deformation patterns are structurally controlled, aligning with bedding and fault orientation. UAV-based monitoring significantly reduces cost ( 70% per point) and enables centimeter to decimeter detection of micro-deformation, providing a reliable basis for slope stability assessment in mining areas. The methodology offering an effective framework for deformation mapping and hazard evaluation.